Cryogenic optical localization provides 3D protein structure data with Angstrom resolution - Weisenburger, Siegfried; Boening, Daniel; Schomburg, Benjamin; Giller, Karin; Becker, Stefan; Griesinger, Christian; Sandoghdar, Vahid (Nature methods, 2017)
We introduce Cryogenic Optical Localization in 3D (COLD), a method to localize multiple fluorescent sites within a single small protein with Angstrom resolution. We demonstrate COLD by determining the conformational state of the cytosolic Per-ARNT-Sim domain from the histidine kinase CitA of Geobacillus thermodenitrificans and resolving the four biotin sites of streptavidin. COLD provides quantitative 3D information about small- to medium-sized biomolecules on the Angstrom scale and complements other techniques in structural biology.
EAM Import::2019-03-13